2022
DOI: 10.24843/ejmunud.2022.v11.i04.p02
|View full text |Cite
|
Sign up to set email alerts
|

Peran Brand Trust Memediasi Brand Image Terhadap Brand Loyalty: Studi Pada Toko Dwipa Umalas Badung

Abstract: Penelitian ini bertujuan untuk menjelaskan peran brand trust memediasi brand image terhadap brand loyalty: pada Toko Dwipa Umalas Badung. Penelitian ini dilakukan kepada pembeli yang berbelanja pada Toko Dwipa, Umals, Badung dengan sample penelitian sebanyak 100 responden dengan teknik sampel non probability sampling dengan metode purposive sampling. Pengumpulan data dilakukan dengan menggunakan kuisioner yang disebarkan secara langsung kepada pembeli Toko Dwipa, Umalas, Badung. Adapun teknik analisis data yan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 5 publications
2
1
0
Order By: Relevance
“…This means that if the application manager wants to increase Jafra's Brand Trust, one effort can be made to improve the Company's Brand Image. The results of this study are the same as those of previous studies conducted by El Nissi & Budiono (2019) and Sastrawan & Pramudana (2022), also showing a positive and significant effect on brand image and trust. The study results show that brand image has no significant effect on customer satisfaction, which is indicated by the p-value (0.237) > 0.05.…”
Section: Path Coefficientssupporting
confidence: 89%
“…This means that if the application manager wants to increase Jafra's Brand Trust, one effort can be made to improve the Company's Brand Image. The results of this study are the same as those of previous studies conducted by El Nissi & Budiono (2019) and Sastrawan & Pramudana (2022), also showing a positive and significant effect on brand image and trust. The study results show that brand image has no significant effect on customer satisfaction, which is indicated by the p-value (0.237) > 0.05.…”
Section: Path Coefficientssupporting
confidence: 89%
“…The more positive the image of a brand, the more positive brand trust will be generated, so consumers carry out more brand loyalty. This is the same as the results of research from Sastrawan & Pramudana (2022) and Rodiques & Rahanatha (2018), where the results of their research explain that brand trust has the potential to be able to significantly mediate brand image and brand loyalty.…”
Section: H4: Halal Awareness Has a Significant Positive Effect On Bra...supporting
confidence: 82%
“…This result shows that the better the brand image, the more positive brand trust will be created, thereby increasing Le Minerale's consumer brand loyalty. This result is supported by research by Sastrawan and Pramudana (2022), which found that a high brand image perceived through good brand trust will increase consumer brand loyalty.…”
Section: Discussionmentioning
confidence: 52%